Psychological characteristics and talent identification in soccer - Morris, T. (Journal of Sports Sciences, 2000)
I review research on psychological characteristics and sports performance and examine the literature on talent identification with particular reference to soccer to derive implications for the use of psychological variables in the talent identification and development process. Although the many cross-sectional studies of psychological characteristics and performance in all football codes conducted over the last 30 years have revealed no clear patterns, studies of both general inventories and specific variables are still being conducted. Reports on talent identification in all codes have increased in recent years, but most are descriptive in nature. In this review, I suggest that research on systematic expert observation has potential asa practical approach, but more studies of this type are needed.Considering the examination of specific psychological variables, only a solitary investigation of creativity in adolescents has shown promise. Further research on creativity and talent identification is required to replicate the positive results found in that study. In summarizing the research on psychological characteristics and talent identification, I conclude that cross-sectional research on adults cannot be extrapolated for use in talent identification with adolescents.I propose that resources would be more effectively used in the provision of psychological skills training for adolescent soccer players, pending more sophisticated research on a wider range of psychological variables. It is recommended that longitudinal or quasi-longitudinal research is essential to determine whether the same psychological variables are important for outstanding performance throughout the process of development and whether psychological variables measured during adolescence can predict outstanding performance in adulthood.